Upaya Peningkatan Pemahaman Terhadap Bahaya Sampah Plastik Dan Pengolahannya Bagi Siswa-Siswi SMA Negeri 3 Kota Kupang, Nusa Tenggara Timur - Anselmus Boy Baunsele; Christiani Dewi Q. M. Bulin; Hildegardis Missa (Universitas Katolik Soegijapranata, 2020)
Plastic waste is a topic that is always discussed in academic studies, especially regarding for the environment. Plastic waste causes natural damage whether it is biotik or abiotik environment. Lack of understanding of the plastic waste dangers caused tless of the environment concern. This is illustrated by the behavoir of throwing plastic waste not on the rubbish bin. By the socialization of plastic waste education and its utilization, it is expected can improve the intellectual understanding about the risk of plastic waste. This activity was initiated by a group of young people in the Kupang city whose joined to the community of